PUSAT PEMASARAN KOPI TORAJA DI MAKASSAR DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Nirhamullah, Nirhamullah; Wasilah, Wasilah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
South Sulawesi is one area which is famous for agricultural products. One result is that the famous spice Coffee. A coffee plantation crops in South Sulawesi, especially in the districts of Tana Toraja promising. That is known by the name